Evaluation of a novel low-cost disposable endoscope for visual assessment of the esophagus and stomach in an ex-vivo phantom model - Garbin, Nicolò; Mamunes, Alexander P.; Sohn, Dennis; Hawkins, Ryan W.; Valdastri, Pietro; Obstein, Keith L. (Endoscopy International Open, 2019)
Background and study aims Our academic lab has developed a novel, low-cost, disposable endoscope for assessment of the esophagus and stomach without need for large equipment or complex electronics. Usability and intuitiveness of the platform are unknown.Methods The novel endoscope (NE) consists of a high-definition camera, LED module, and three bellows. Compressed air actuates the bellows, producing camera/LED articulation. Insufflation and lens cleaning ports are present. Video can be displayed on any monitor. Total material costs less than $ 35 US. Five novices, five fellows, and five attendings performed five trials using a conventional endoscope and the NE on an upper tract phantom with six gastric landmarks marked. Outcomes included successful identification and time to landmarks; and intuitiveness (NASA task load index; user comments). Results All landmarks were successfully identified with both endoscopes for all trials (n = 900). Attendings and fellows were quicker with the conventional endoscope when compared to the NE (24.48 v 37.13s; P < 0.01). There was no significant time difference between platforms for novices (P = 0.16). All users found the NE intuitive with low mental and physical demand. Novices reported lower temporal demand and effort when using the NE.Conclusions The NE was easy to maneuver, intuitive, and successful at visualizing gastric landmarks. All users were pleased with the NE drive mechanism and were successful at visualizing the gastric landmarks in a clinically acceptable time. The novel platform has the potential to facilitate rapid, low-cost, diagnostic assessment of the esophagus and stomach in non-traditional settings – facilitating patient management decisions, minimizing encumbrance, and avoiding cross-contamination.